(untitled) (Journal on studies and research of academic knowledge, 2022)
In this essay, an analysis of the importance of the teaching of Mathematics at the different levels of formal education is carried out, for which a bibliographical review of various publications referring to mathematical education and learning evaluations has been carried out in the areas observed in the educational context of Paraguay; the methodology used consisted in the application of a meta-analysis of the bibliographical references, this allowed to analyze the reality of mathematics education in Paraguay, especially in relation to the research on the subject that has been developed in recent years. The results of the review shows that it is necessary to have a greater amount of research, they can be either bibliographical or experimental, on the results of mathematics education in the country, considering that if there is any, it is not null, very low scientific production on topics such as the didactics of geometry, or statistics and probability, which are two very important areas in the building of mathematical knowledge within young people.